2012
DOI: 10.1128/jvi.07173-11
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the Genetic Diversity of a Virus Family: Approach and Evaluation through a Case Study of Picornaviruses

Abstract: The recent advent of genome sequences as the only source available to classify many newly discovered viruses challenges the development of virus taxonomy by expert virologists who traditionally rely on extensive virus characterization. In this proof-ofprinciple study, we address this issue by presenting a computational approach (DEmARC) to classify viruses of a family into groups at hierarchical levels using a sole criterion-intervirus genetic divergence. To quantify genetic divergence, we used pairwise evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 72 publications
2
77
0
Order By: Relevance
“…We concluded that the alignment used in our study contains information compatible with taxonomy. Hence, we used this alignment as input for DEmARC in order to devise the GENETIC classification of picornaviruses (43). We identified three statistically most strongly supported positions of discontinuity (thresholds) in the picornavirus PED distribution that we assigned as defining species, genus, and supergenus levels of the classification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the alignment used in our study contains information compatible with taxonomy. Hence, we used this alignment as input for DEmARC in order to devise the GENETIC classification of picornaviruses (43). We identified three statistically most strongly supported positions of discontinuity (thresholds) in the picornavirus PED distribution that we assigned as defining species, genus, and supergenus levels of the classification.…”
Section: Resultsmentioning
confidence: 99%
“…We have developed DEmARC, a quantitative procedure for hierarchical classification of a virus family based on intervirus genetic divergence (43). It has been evaluated extensively for consistency and stability with respect to key parameters including the amount and/or diversity of the input data, the alignment construction method, and the measure of intervirus divergence.…”
Section: Methodsmentioning
confidence: 99%
“…Formalized clustering and network analysis methods that create similarity metrics that are based on the detection of homologous genes and their genetic divergence [55][56][57] could be valuable for taxonomic assignments and should be critically evaluated for their effectiveness in the development of a robust classification approach. Frameworks of this kind may have to be tailored to the virus group.…”
Section: Proposed Taxonomymentioning
confidence: 99%
“…Despite these various issues, pairwise-identity-based virus classification criteria are extremely popular amongst virus taxonomists and are likely to grow in importance due to how easy they are to use and the fact that, once properly validated, they accurately reflect the biology of these organisms [2,32,33]. We have therefore devised a pairwise-identity-based approach for mastrevirus classification that almost completely removes all the alignment and gaphandling problems of the current ICTV-endorsed mastrevirus classification protocol.…”
Section: Introductionmentioning
confidence: 99%